Mobility histories of 7th–9th century AD people buried at early medieval Bamburgh, Northumberland, England. Issue 3 (4th June 2013) - Groves, S.E.; Roberts, C.A.; Lucy, S.; Pearson, G.; Gröcke, D.R.; Nowell, G.; Macpherson, C.G.; Young, G.
ABSTRACT Early Medieval England is described historically as a time when people migrated from the Continent to English shores. This study tests the hypothesis that those buried in the Bowl Hole cemetery, Bamburgh, Northumberland were nonlocally born, because of its royal status. Ninety‐one male and female adult, and nonadult, skeletons were studied. Isotope ratios of strontium (87Sr/86Sr) and oxygen (δ18O) were generated for 78 individuals (28 females, 27 males, five "adults, " 18 nonadults). The mean Sr value for human enamel was 0.71044, standard deviation (sd) 0.001, and the mean O (δw) value is −5.9‰, sd 1.6‰. Additionally, animal tooth enamel (mean Sr value 0.710587, sd 0.001; mean O value −6.5‰, sd 1.5‰), local soil (mean Sr value 0.709184, sd 0.0006), snail shells (mean Sr value 0.708888, sd 0.0001), and soil samples from a 5 km transect heading inland (mean Sr value 0.709121, sd 0.0003), were analyzed for an indication of the isotopic composition of bioavailable Sr in the modern environment and to assess the impact of sea‐spray; water samples from a well, local rivers, and standing water were analyzed for local δ18O values (mean O value −6.4‰, relative to VSMOW, sd 2.8‰). Over 50% of those buried at Bamburgh were nonlocal. All ages and both sexes produced "nonlocal" signatures; some suggested childhood origins in Scandinavia, the southern Mediterranean or North Africa. Stature and other indicators of health status indicated differences in quality of life between local and migrant groups. These differences did not extend to burial practices. Am J Phys Anthropol 151:462–476, 2013.© 2013 Wiley Periodicals, Inc.